2010
DOI: 10.1002/ps.1988
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the toxicity of 17 essential oils against Choristoneura rosaceana (Lepidoptera: Tortricidae) and Trichoplusia ni (Lepidoptera: Noctuidae)

Abstract: Based on these results, patchouli oil and other essential oils have sufficient efficacy to be considered as components of an essential oil-based insecticide that targets these lepidopteran pests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 32 publications
1
27
0
1
Order By: Relevance
“…In studies of evaluating essential oils against lepidopteron larvae, patchouli oil was found to be the most toxic to oblique banded leafroller ( Choristoneura rosaceana ) larvae (LC 50 = 2.8 µl/ml and LD 50 = 8.0 µg/insect, whereas garlic oil was the most toxic to Trichoplusia ni larvae (LC 50 = 3.3 µl/ml and LD 50 = 22.7 µg/insect), followed by patchouli oil and lemongrass oil (Machial et al 2010). In another study, essential oils of Thymus vulgaris (LC 50 = 4.8 mg/ml), Syzygium aromaticum (LC 50 = 6.0 mg/ml), Cymbopogon citrates (LC 50 = 7.7 mg/ml), Cinnamomum cassia (LC 50 = 8.5 mg/ml), Cymbopogon nardus (LC 50 = 10.1 mg/ml) were found toxic to T. ni larvae in residual bioassays (Jiang et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In studies of evaluating essential oils against lepidopteron larvae, patchouli oil was found to be the most toxic to oblique banded leafroller ( Choristoneura rosaceana ) larvae (LC 50 = 2.8 µl/ml and LD 50 = 8.0 µg/insect, whereas garlic oil was the most toxic to Trichoplusia ni larvae (LC 50 = 3.3 µl/ml and LD 50 = 22.7 µg/insect), followed by patchouli oil and lemongrass oil (Machial et al 2010). In another study, essential oils of Thymus vulgaris (LC 50 = 4.8 mg/ml), Syzygium aromaticum (LC 50 = 6.0 mg/ml), Cymbopogon citrates (LC 50 = 7.7 mg/ml), Cinnamomum cassia (LC 50 = 8.5 mg/ml), Cymbopogon nardus (LC 50 = 10.1 mg/ml) were found toxic to T. ni larvae in residual bioassays (Jiang et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Investigations of structureactivity relations have yielded little predictive value in this regard (Rice and Coats 1994;Tsao et al 1995). We recently screened 17 commercially available plant essential oils for contact toxicity to the cabbage looper and to the obliquebanded leafroller (Choristoneura rosaceana, Tortricidae), and important fruit pest in North America (Machial et al 2010). For the cabbage looper the most toxic oils were those from garlic (Allium sativum, Alliaceae), lemongrass (Cymbopogon nardus), and patchouli (Pogostemon cablin, Lamiaceae), whereas for the leafroller the most active oils were those from patchouli and thyme (Thymus vulgaris).…”
Section: Relationship Between Chemical Composition and Bioactivity Inmentioning
confidence: 99%
“…Variations in chemical composition owing to seasonal or geographic differences, growth conditions, and extraction methods for thyme (Thymus vulgaris L.) essential oil (Senatore 1996;Hudaib et al 2002;Asllani and Toska 2003) and lemongrass (Cymbopogon citratus Stapf.) essential oil (Zheljazkov et al 2011;Desai et al 2014;Moncada et al 2014) are well documented, along with their insecticidal activity (Lee et al 2001;Machial et al 2010;Jiang et al 2012), repellence (Diaz-Montano andTrumble 2013;Zhang et al 2013), and physiological impact such as insect larval growth or feeding deterrence (Hummelbrunner and Isman 2001;Jiang et al 2012) as well as acaricidal activity (Sertkaya et al 2010). Although many screening data highlighted the merit of both essential oils as insect control agents, understandings of the activities of individual constituents and their comparative contributions to the overall toxicity are vital in the considerations of candidate oils as for practical use (i.e., determinations of cultivation condition, commercialization, or quality control).…”
Section: Introductionmentioning
confidence: 99%